Microwave promoted solvent-free one-pot synthesis of N,N `-disubstituted urea derivatives - Jadhav, Vinod H.; Deshpande, S. S.; Borate, Hanumant B.; Wakharkar, R. D. (Journal of Chemical Research-S, 2005)
An efficient one-pot synthesis of N,N -disubstituted urea derivatives from substituted anilines, ethyl chloroformate and methyl anthranilate or methyl 3-amino-2-butenoate under microwave irradiation is reported.
Keywords: Anilines; methyl 3-amino-2-butenoate; methyl anthranilate; Microwave; urea derivatives